2010
DOI: 10.3354/meps08682
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment promotes learning in fish

Abstract: Captive birds and mammals reared in enriched rearing environments have been shown to behave more flexibly compared to animals reared in impoverished or plain environments. Recent evidence has shown that this is also true for fish; enrichment promotes faster recovery after a stressful experience, a higher propensity for exploration of novel areas and the development of more sophisticated social behaviour. Here we report how enrichment influences social learning in juvenile cod Gadus morhua that were reared in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 42 publications
3
71
0
3
Order By: Relevance
“…In addition, Kotrschal and Taborsky (Kotrschal and Taborsky, 2010) showed that environmental changes during rearing can affect later outcomes in cognitive abilities. Strand et al (Strand et al, 2010) also suggested that enrichment of the environment could increase learning in fish. We wondered what effects social experience gained by age (chronological time spent in social interactions) and rearing conditions (complexity of rearing environment) would have on social dominance.…”
mentioning
confidence: 99%
“…In addition, Kotrschal and Taborsky (Kotrschal and Taborsky, 2010) showed that environmental changes during rearing can affect later outcomes in cognitive abilities. Strand et al (Strand et al, 2010) also suggested that enrichment of the environment could increase learning in fish. We wondered what effects social experience gained by age (chronological time spent in social interactions) and rearing conditions (complexity of rearing environment) would have on social dominance.…”
mentioning
confidence: 99%
“…As reviewed in Näslund and Johnsson (2014), there are several studies demonstrating the positive effects of environmental enrichment on welfare across many fish species. Compared with captive-held fish in barren environments, those provided with some form of enrichment have been found to have increased brain development (Marchetti and Nevitt, 2003;Kihslinger and Nevitt, 2006;von Krogh et al, 2010;Salvanes et al, 2013), reduced impact from stressors (Braithwaite and Salvanes, 2005;Naslund et al, 2013;Batzina et al, 2014), improved foraging ability (Brown et al, 2003;Strand et al, 2010;Rodewald et al, 2011), improved post-release survival (D'Anna et al, 2012) and positive effects on growth (Leon, 1975;Hansen and Moller, 1985;Batzina et al, 2014). This general increase in neural plasticity results in the development of behaviourally flexible fish that are better at coping with a variety of situations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is evidence that fish can learn [e.g. associative learning (Bratland et al, 2010;Siebeck et al, 2009), social learning (Strand et al, 2010)] (reviewed by Kieffer and Colgan, 1992;Bshary et al, 2002) and remember (e.g. Harvey-Girard et al, 2010;Nordgreen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%